Prevalence and associated variables of post‐dialysis fatigue: Results of a prospective multicentre study. Issue 6 (10th June 2018) - Bossola, Maurizio; Marzetti, Emanuele; Di Stasio, Enrico; Monteburini, Tania; Cenerelli, Stefano; Mazzoli, Katia; Parodi, Emanuele; Sirolli, Vittorio; Santarelli, Stefano; Ippoliti, Fabio; Nebiolo, Pier Eugenio; Bonomini, Mario; et al.
Abstract: Aim: The study aims to determine prevalence and severity of PDF and to define its associated variables. Methods: In five haemodialysis units of northern‐centre Italy, patients were regarded to suffer from PDF if they spontaneously offered this complaint when asked the open‐ended question: Do you feel better or worse after dialysis? If worse, please specify in which way. A complaint of fatigue would be probed further with questions directed at its duration, frequency and intensity, allowing creation of a fatigue index of severity (one third of the sum of these three parameters, each rated from 1 to 5). Patients were stratified into three groups according the severity of PDF: 1) score = 0; 2) score = 1–3; 3) score > 3. Results: We studied 271 patients: 164 had PDF and 107 did not. PDF patients had significantly longer time of recovery after dialysis (TIRD). TIRD was significantly associated with PDF duration, intensity, and frequency. Patients with PDF were older and had a lower ADL score. At multivariate analysis, PDF was significantly associated with TIRD. In a multivariate model that did not include TIRD, PDF was independently associated with age and ADL. Sixty patients had moderate PDF and 104 had severe PDF. In patients with severe PDF, age and dialytic age were higher, ADL and IADL scores were lower, TIRD was longer and the ultrafiltration rate was lower. At multivariate analysis, PDF severity was independently associated with TIRD. In the model without TIRD, PDF severity was associated with ADL only. Conclusion: Post‐dialysis fatigue is frequent and associated with age and ADL. Dialytic variables seem unrelated to PDF. Summary at a Glance: This study shows post dialysis fatigue is associated with patients' age and ADL, and not with dialytic variables.